(untitled) (مجلة دراسات وبحوث إعلامية, 2025)
Conciseness and telegraph–like writing are frequent features of news headlines. These titles are usually intended to give readers a glimpse of what the underneath news stories are about. But sometimes, the headlines are vague intentionally or unintentionally. The vagueness is either writer- oriented or reader-oriented. The current study is an endeavor to investigate the reasons behind vagueness whether on the part of the author (SLT), or on the part of the translator (TLT). It is hypothesized that most vagueness is caused by the way titles are written. The recognition of meaning of headlines is sometimes poses a problem for unskillful translators, as is the case in our MA candidate subjects, especially when it is related to acronyms and abbreviations newly coined, in addition to some other kinds of lexical vagueness. The study concludes that the main reason behind vagueness of headlines as far as the translators in this study are concerned is the unacquaintedness in this field of translation, especially we live in an accelerated world in terms of the current events in all fields and what they are accompanied with of new terms, abbreviations and acronyms which flush in all of a sudden in a way that one cannot cope with immediately sometimes.